Electrochemical investigation of carbon and metal-oxide as additives to the negative electrode of lead-acid battery - Fernandez, Matthew M.; Diaz, Leslie Joy L. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The increasing demand of cycle life performance of Pb-acid batteries requires that improvement of the negative Pb electrodes charge capacity. Electrochemical investigations were performed on Pb electrode, Pb+Carbon (Carbon black and Graphite) and Pb+Metal-Oxide (Titanium Dioxide and Montmorillonite) electrodes to evaluate the ability of the additives to enhance the electrochemical faradaic reactions that occur during the actual charge and discharge of Pb-acid battery negative electrode. The electrodes were characterized through electrochemical techniques such as Cyclic Voltammetry (CV), Potentiostatic Polarization, Chrono Charge and Discharge, Potentiodynamic Polarization, and Electrochemical Impedance Spectroscopy (EIS). Cyclic voltammograph revealed that the addition of carbon to the Pb electrode has significant effect on the peak current density, anodic charge and cathodic charge capacities, shifted the anodic and cathodic peak potentials, and formed secondary anodic peaks.Addition of Carbon Black 1 on the Pb electrode even at low amount (0.01) increased the peak current density, anodic charge and cathodic charge capacities by tenfold. Increasing weight percentage of Carbon Black 1 on homogenous mixture of Carbon Black 1 and Carbon Black 2 increased the anodic and cathodic electrochemical faradaic reactions of the Pb electrode, and magnitude of charge and discharge values. The current enhancement with respect to Carbon Black 1 are twice higher than Carbon Black 2. Potentiostatic polarization measurements revealed that the total passivating time to cover the active surface with PbSO4 crystals were the same for all the electrodes but the peak current densities were different.
Thesis (M.S. Metallurgical Engineering)--University of the Philippines Diliman
Keywords: Lead-acid batteries